2000
DOI: 10.1016/s0024-3795(00)00065-3
|View full text |Cite
|
Sign up to set email alerts
|

Commuting pairs and triples of matrices and related varieties

Abstract: In this note, we show that the set of all commuting d-tuples of commuting n × n matrices that are contained is an n-dimensional commutative algebra is a closed set, and therefore, Gerstenhaber's theorem on commuting pairs of matrices is a consequence of the irreducibility of the variety of commuting pairs. We show that the variety of commuting triples of 4 × 4 matrices is irreducible. We also study the variety of n-dimensional commutative subalgebras of M n (F), and show that it is irreducible of dimension n 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…It was proved by Motzkin and Taussky [13] (see also Guralnick [7]), that the variety of pairs of commuting matrices was irreducible. It was Guralnick [7] who showed that this is no longer the case for the variety of triples of commuting matrices (see also Guralnick and Sethuraman [8], Holbrook and Omladič [11], Omladič [14], Han [10],Šivic [16]). Recently, it was proved that the variety of commuting pairs of nilpotent matrices was irreducible (Baranovsky [1], Basili [2]).…”
Section: Introductionmentioning
confidence: 99%
“…It was proved by Motzkin and Taussky [13] (see also Guralnick [7]), that the variety of pairs of commuting matrices was irreducible. It was Guralnick [7] who showed that this is no longer the case for the variety of triples of commuting matrices (see also Guralnick and Sethuraman [8], Holbrook and Omladič [11], Omladič [14], Han [10],Šivic [16]). Recently, it was proved that the variety of commuting pairs of nilpotent matrices was irreducible (Baranovsky [1], Basili [2]).…”
Section: Introductionmentioning
confidence: 99%
“…So B + tX commutes with C for all t ∈ F. Moreover for t = 0, the matrix B + tX has more than one point in the its spectrum. By Lemma 2.4, the triple (A, B + tX, C) belongs to G (3,7) for all t ∈ F, t = 0.…”
mentioning
confidence: 94%
“…Guralnick [2] had proved that C(3, n) is reducible for n ≥ 32, but irreducible for n ≤ 3. Using the results from [7], Guralnick and Sethuraman [3] had proved that C(3, n) is irreducible when n = 4.…”
mentioning
confidence: 99%
See 2 more Smart Citations